PELAKSANAAN SENAM HAMIL YOGA UNTUK KESIAPAN IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN DI PUSKESMAS PUTRI AYU TAHUN 2019 - Gustina Gustina (Jurnal Abdimas Kesehatan (JAK), 2019)
Backround: One of antenatal care to do a quality approach is physical exercise, such as meditation / yoga. Practicing pregnant yoga exercises at this time is one of the self help solutions that support the process of pregnancy, birth and even childcare that can be done in antenatal classes. care, which is a means for group learning about maternal health, in the form of face-to-face aimed at increasing knowledge and skills abouth pregnancy, childbirth, postpartum care and newborn care (Depkes, 2010).Target and uotcom: Third pregnant women in the field antenatal care, aim for improve pregnant yoga for readiness face up childbirth. Method implementation:Implementation administrative preparation, sociaization, evaluation. Results : Before doing yoga pregnancy exercise as many as 7 mothers were ready to give birth, 2 people were hesitant, and 1 person was afraid to face childbirth. After doing yoga exercise, the result: there are still doubts about 1 person, ready for 2 people and more ready for7 people. Conclusion: The results before and after the yoga pregnancy exercise can be concluded that there is a change in the readiness of mothers in facing physical and psychological labor. Suggestion : Health centre carry out pregnancy exercise regularly scheduled yoga for pregnant women, especially pregnant third trimester